PENGENALAN DAN PENJELAJAHAN KEARIFAN LOKAL KALIMANTAN SELATAN MELALUI METODE PERMAINAN EDUKATIF - Agustina, Lili; Kasmilawati, Isna; Lestari, Nana Citrawati (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
The educational institution partnering in this Community Service Program is SDN Telaga Biru 1 Banjarmasin. The primary issue faced by this institution is the lack of students' awareness and understanding of the local wisdom in South Kalimantan. In this community service activity, the proposers, in collaboration with the partner institution, agreed to prioritize the problem of limited integration of local wisdom into the learning process and the lack of diverse teaching methods in the classroom to introduce local wisdom to students. These limitations make students less interested in learning about South Kalimantan's local wisdom. Integrating local wisdom into school learning plays a significant role in providing students with positive experiences in understanding the values of their region's local wisdom. This program was conducted through socialization and simulation activities using educational games as a teaching method. This approach was chosen to facilitate students' understanding and increase their interest in local wisdom. The results of the activity showed that the use of educational games received positive responses from students in learning about and preserving the local wisdom of South Kalimantan. This activity underscores the importance of integrating local wisdom into the learning process as a strategy for cultural preservation and improving educational quality